The Global Nursing Migration Crisis: A Review Of Socioeconomic, Ethical, And Policy Dimensions Impacting Healthcare Sustainability (The Review of Diabetic Studies, 2025)
The global nursing migration crisis has emerged as a critical challenge to healthcare sustainability, particularly in the wake of escalating health workforce shortages and widening socioeconomic disparities. This review paper examines the complex interplay of socioeconomic, ethical, and policy factors driving the international migration of nurses, with a focus on its implications for both source and destination countries. Drawing from recent literature, global health reports, and policy analyses, the paper synthesizes evidence on the causes, consequences, and potential solutions to this growing phenomenon. Socioeconomic drivers remain the most prominent catalysts of nurse migration. Push factors such as low wages, poor working conditions, limited professional development opportunities, and political instability compel nurses to seek employment abroad. Conversely, pull factors—including higher salaries, advanced training, better infrastructure, and immigration incentives—make high-income countries attractive destinations. While remittances from migrant nurses contribute to household income and national economies, they do not compensate for the systemic loss of skilled professionals in source countries, where health systems are often fragile and understaffed. Ethical concerns surrounding nurse migration are increasingly debated in global health discourse. The depletion of nursing workforces in low- and middle-income countries raises questions about distributive justice, equity, and the right to health. Ethical tensions also arise between respecting individual autonomy and protecting collective healthcare needs. Recruitment practices, particularly those targeting vulnerable populations or bypassing national workforce planning, further complicate the ethical landscape. Policy responses to nursing migration have been fragmented and inconsistent. While the World Health Organization’s Global Code of Practice on the International Recruitment of Health Personnel provides a framework for ethical recruitment, its voluntary nature limits enforcement. National policies vary widely, with some countries actively recruiting foreign nurses while others impose migration restrictions. The COVID-19 pandemic has intensified migration trends, exposing the fragility of health systems and the urgent need for coordinated global action. This review concludes that sustainable solutions to the nursing migration crisis require a multifaceted approach: strengthening domestic health systems, enforcing ethical recruitment standards, and fostering international cooperation. Addressing these challenges is essential not only for protecting the rights of nurses but also for ensuring equitable and resilient healthcare delivery worldwide.